Mineral magnetic properties of sediments of beaches, Redi-Vengurla coast, central west coast of India: A Seasonal Characterization and Provenance Study - Gawali, P. B.; Basavaiah, N.; Hanamgond, Pramod T. (My University, 2010)
The beaches under study are characterized by distinctly different magnetic signatures in terms of their concentration and magnetic grain sizes. Seasonal variation in accumulation and erosion is seen at Vengurla Beach (Stations 1–7), which is moderate to very low premonsoon, high to low during monsoon season, and low to very low postmonsoon. Presence of fine single domain magnetic grains is moderate to high premonsoon, moderate to low during monsoon, and low postmonsoon at stations 1, 4, 7 (Vengurla beach), and 8 (Aravali beach). Aravali Beach has a very low concentration of magnetic minerals, precluding realistic assessment of its seasonal accretion–erosion pattern. At Redi Beach (Stations 15–20), the concentration levels of magnetic minerals are high premonsoon, which further increases during monsoon season, although at certain locations the rise continues postmonsoon. The sediments of these three beaches have variable proportions of magnetite, titanomagnetite, and hematite. The concentration of magnetic minerals is more at the northern (Stations 1 and 2) and southern (Stations 16–19) ends of Vengurla and Redi beaches, respectively. The provenance of magnetite and titanomagnetite can be attributed to Deccan traps and relict sands. This technique can complement the conventional methods and underlines the utility of magnetic parameters in studying sediment movement along the beaches.
Keywords: Magnetic susceptibility; Frequency-dependent susceptibility; Magnetic minerals; Beach sediments; Ferrimagnets; Maharashtra; West Coast; India